Developing Innovative Work Behaviour: The Influence of Entrepreneurial Leadership through Creative Self-Efficacy and Employee Engagement - Indriyani, Ratih; Natajaya, Richie; Palumian, Yonathan (Universitas Maarif Hasyim Latif, 2024)
Salesperson is important to support the development of property service companies in Surabaya. Salesperson needs to haveinnovative performance behavior to achieve maximum performance. To form innovative work behavior, entrepreneurialleadership is needed along with creative self-efficacy and employee engagement levels. The purpose of this study was todetermine the effect of entrepreneurial leadership with creative self-efficacy and employee engagement as mediating variableson innovative work behavior in property salespersons in Surabaya. The type of research used is quantitative research with acausal nature and the sampling technique uses non-probability sampling technique with purposive sampling method. The sampleused was 114 respondents. This study uses PLS data analysis technique. The results of the study showed that entrepreneurialleadership has a significant effect on innovative work behavior, creative self-efficacy, and employee engagement. Creative self-efficacy and employee engagement have a significant effect on innovative work behavior, and creative self-efficacy and employeeengagement successfully mediate between entrepreneurial leadership and innovative work behavior.